Phonologisches Bewusstsein bei einem polnisch-amerikanischen Kind mit Legasthenie. Eine Fallstudie - Rafał Młyński; Agata Guzek (Linguistische Treffen in Wrocław)
The case study is focused on phonological awareness in Polish and English of a bilingual child with a diagnosis of dyslexia. The choice of this topic was dictated by a paucity of studies focusing on Polish-other bilingualism in Polish literature. The theoretical portion of the article includes information regarding phonological awareness and its relationships with dyslexia and bilingualism. The empirical portion contains the methodology, assessment instruments, data analysis, and their interpretation chosen by the authors. In addition, information on the subject’s language use was included. There were 3 research questions formulated: 1) What are the qualitative and quantitative characteristics of syllable segmenting and blending in Polish and English in a bilingual child with SRD? 2) What are the qualitative and quantitative characteristics of phoneme segmenting and blending in Polish and English in a bilingual child with SRD? 3) What is the phonological memory capacity in both languages in a bilingual child with SRD? The “unknown language” test was used to collect data, while the language biography method and the classification of errors made by persons with dyslexia were used for the analysis. The data were analyzed qualitatively and quantitatively. They revealed deficits in segmenting and blending of sounds and syllables in both languages. The errors made by the subject on the segmenting and blending of phonemes tasks were syntagmatic – they indicated deficits in the linear evaluation of auditory stimuli. This type of errors is typical for dyslexia defined as a disorder of linear processing of linguistic information. In addition, the subject presented with significant difficulties with his phonological memory across languages. These results are indicative of the need to enroll the boy in speech-language therapy and reading interventions focusing on the deficits common in dyslexia. The therapy should be in both languages and address phonological and neurobiological skills. Additionally, reading training in Polish and English should also be conducted.